2011
DOI: 10.1007/s11199-011-9935-2
|View full text |Cite
|
Sign up to set email alerts
|

Muscularity Beliefs of Female College Student-Athletes

Abstract: Female athletes in the United States face the paradoxical challenge of acquiring a degree of muscularity to be successful in their sport, yet they also endure pressure from societal expectations of femininity that often don't conform with the notion of muscularity. To address research questions about how female student-athletes balance muscularity and femininity, we conducted a mixed-methods study to examine muscularity beliefs among female student-athletes, female college students, and male college student-at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 54 publications
9
36
1
Order By: Relevance
“…So, if a onetime 30-minute magazine exposure negatively affects women's body size perception, it seems a 30-minute exposure to television programs and advertisements may invoke similar negative effects on body image. This partially supports the second hypothesis -both men and women who read more magazines and watch more television displayed a higher drive for muscularity -and aligns with previous researchers' findings that media equates female sexiness to a thin and toned body (Choi, 2000;Gruber 2007;Homan et al, 2012;Steinfeldt et al, 2011). As women are exposed to these thin but toned images their body dissatisfaction and drive for muscularity increases.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…So, if a onetime 30-minute magazine exposure negatively affects women's body size perception, it seems a 30-minute exposure to television programs and advertisements may invoke similar negative effects on body image. This partially supports the second hypothesis -both men and women who read more magazines and watch more television displayed a higher drive for muscularity -and aligns with previous researchers' findings that media equates female sexiness to a thin and toned body (Choi, 2000;Gruber 2007;Homan et al, 2012;Steinfeldt et al, 2011). As women are exposed to these thin but toned images their body dissatisfaction and drive for muscularity increases.…”
Section: Discussionsupporting
confidence: 87%
“…The gender difference in the relationships between television viewing and the drive for muscularity between sexes could be attributed to women's internalization of a paradoxical media ideal. Women's drive for muscularity is marked by women's desire to be toned but thin (Choi, 2000;Gruber, 2007;Homan et al, 2012;Steinfeldt et al, 2011). This finding fits with the ideal body of contemporary female models, actors, and athletes -which are slender with muscle definition.…”
Section: Discussionmentioning
confidence: 66%
“…Their appreciation changes when we add the meaning of the results of item 7, where strong gender stereotypes appear in the responses related to the existence of a decrease in the physical attractiveness of the female athlete due to their muscular development. This reaffirms studies such as the ones from Steinfeldt (2011), where the degree in which women athletes wanted to be muscular was empirically assessed as well as their reasons. They indicated that they wanted to be muscular enough to succeed in athletic events but at the same time they did not want to have a excessive volume of musculature that would break their image of femininity.…”
Section: Female Body and Muscle Developmentsupporting
confidence: 79%
“…In this regard, the work of Steinfeldt (2011) indicates that women athletes want to be "sufficiently muscular" to succeed in the athletic events but at the same time, not to have excessive volume of musculature that breaks their image of femininity. It means that their body development has an eminently functional nature.…”
Section: Introductionmentioning
confidence: 99%
“…But what happens with women who endorse a non-traditional female ideology? Although there are not many studies about the relationship between pursuit of muscularity and women, it has been found that female studentathletes, who are less feminine than "normal" girls, report significantly higher pursuit of muscularity scores than female students (Steinfeldt, Carter, Benton, & M. Steinfeldt, 2011). For this reason, it is expected that women with low scores in a gender ideology scale should report more drive for muscularity than those who score high in the same scale.…”
Section: Pursuit Of Muscularitymentioning
confidence: 99%